Properties of ground water in north part of Qatar, hydrological, hydro chemical studies, uses and issues, Qatar - Al-naimi, Latifa (Journal of agricultural, environmental and veterinary sciences, 2017)
As ground water is the only water source, then there is utmost need for exploring ground water aquifer besides importing water from neighboring countries and imposing serve strains on the available ground water resources. The present work deals with the hydrogeology, hydro geophysics, hydro chemistry, ground water management and planning in Qatar Peninsula.. For this purpose, field trips were carried out to measure geo-electrical properties of the rock units composing the geologic successions, and to measure the depth of water and deduction of ground water level for selected and test wells tapping the already proved aquifers (Dammam, Rus, Umm er Radhuma aquifers). In addition, ground water samples from the chosen wells have been collected for chemical analysis. A brief description of the geology of Qatar is included in this work with special attention to the lithology of water bearing formations, and the impact of structure on the hydrogeological conditions. The study of subsurface geological conditions of Qatar Peninsula has been made through the interpretation of geo electrical surveying data. 19 vertical electrical soundings (VESes) were conducted in the area of study. The interpreted geo electric measurements were correlated with the available information of some boreholes. The study of the hydro chemical conditions of the ground water aquifers of Qatar is mainly based on the chemical analysis of water samples collected by the present author. Total dissolved solids (TDS), major cations, major anions (Na+, Cl-, Ca+2, SO4-2, Mg+2, CO3-2, HCO3-) and PH were determined. In addition, hydro chemical coefficients were calculated to identify the origin of ground water and the suitability of ground water for irrigation purposes. The present study aims to: Identify the sub surface geological condition necessary for clarifying the hydrogeological conditions of Qatar Peninsula. And Studying the collective hydrogeological conditions of Qatar Peninsula in the light of new data and detailed information enabling the possibility of additional ground water resources and proposing hydrogeological map for Qatar. And Planning ground water resources with the aim of maximizing water utility in the light of ground water quantity and quality. The study of some area in north of Qatar state presents results of water geochemical analysis in aquifers, the change in water table and salinity in wells. Based on samples of water ranges between 1500-12000 ppm in salinity (TDS), water table ranges 35-200m in depth. This study makes the best useful way to use it for several fields according to many factors. Major anions and cations are useful indicators of geochemical and availability of water in aquifers, the suitable units for irrigation water and human uses range between 1000-5000 ppm, that problem effect on surface uses. Geological study shows the lithology, composition, thickness and structure of layers, which contain water. About three main aquifers in Qatar (Umm er Radahma aquifer Paleocene, Rus formation aquifer Eocene, Dammam formation aquifer Eocene). Geophysics methods support geological studies for detailed information about water table and extension of aquifer. Lithology and structure for aquifer in Qatar play important role in retention of water between layers. Main results for geochemical sample of water and mapping for water table between aquifers are important to consider in the interpretation data from aquifer, serving to remind us of the different uses underground water.